Compact digital holoscope with dual wavelength - Di, Jianglei (2013)
Digital holography allows fast, nondestructive, full-field 3D measurement of reflecting as well as transmitting objects. It is a well-established two-step method of digital recording and numerical reconstruction of the full complex field of wavefront. It has found applications in diverse fields, such as micro-optics and MEMS metrology, cell imaging and particle characterization. However, for quantitative phase measurement there is 2π by phase ambiguities that limit measurements of optical path lengths to the wavelength of the illumination light. For continuous profiles, phase unwrapping is used to overcome the phase jumps. One approach is to use a synthetic wavelength using two lasers with different wavelengths. This synthetic wavelength would depend on the wavelengths of the two sources and thus can be tuned by selecting appropriate sources. In this paper, this concept is integrated into the compact digital holoscope which provides the system with the capability of measuring over a range of step heights from the nanometer to the micrometer realm. Applications of the system for reflecting geometries is discussed.